Deep eutectic solvents skeleton typed molecularly imprinted chitosan microsphere coated magnetic graphene oxide for solid‐phase microextraction of chlorophenols from environmental water. Issue 6 (9th January 2020) - Li, Guizhen; Row, Kyung Ho
Abstract: Novel molecularly imprinted chitosan microspheres were prepared on the surface of magnetic graphene oxide, with deep eutectic solvents both as a functional monomer and template. The prepared molecularly imprinted chitosan microspheres‐magnetic graphene oxide was characterized by scanning electron microscopy, Fourier transform infrared spectroscopy, X‐ray diffraction,  Brunauer‐Emmett‐Teller surface area, thermogravimetric analysis were subsequently combined with solid‐phase micro‐extraction for simultaneous separation and enrichment of the extraction of chlorophenols from environmental water. Factors affecting the extraction efficiency of chlorophenols were optimized using response surface methodology. The actual extraction capacities under the optimal conditions (liquid to solid ratio = 3, cycles of adsorption/desorption = 5, 40°C extraction temperature, and extraction time for 35 min) were 86.90 mg/g. Compared to the traditional materials, the molecularly imprinted chitosan microspheres‐magnetic graphene oxide produced higher selectivity and extraction capacity.